Magnetofluorescent Nanoprobe for Multimodal and Multicolor Bioimaging. (27th October 2020) - Yadav, Aditya; Rao, Chethana; Verma, Navneet Chandra; Mishra, Pushpendra Mani; Nandi, Chayan Kanti
Although, superparamagnetic iron oxide nanoparticles (SPIONs) have extensively been used as a contrasting agent for magnetic resonance imaging (MRI), the lack of intrinsic fluorescence restricted their application as a multimodal probe, especially in combination with light microscopy. In Addition, the bigger size of the particle renders them incompetent for bioimaging of small organelles. Herein, we report, not only the synthesis of ultrasmall carbon containing magneto-fluorescent SPIONs with size ∼5 nm, but also demonstrate its capability as a multicolor imaging probe. Using MCF-7 and HeLa cell lines, we show that the SPIONs can provide high contrast mulicolor images of the cytoplasm from blue to red region. Further, single particle level photon count data revealed that the SPIONs could efficaciously be utilized in localization based super resolution microscopy in future.